Factors Of Old Neighbourhood Environment Affecting The Physical And Mental Health Of The Elderly Living In Skipped-Generation Households In Guangzhou, China - Zhu, Yonglin (2025)
With the deepening of urbanization, the urban development strategy of many large cities in china has changed from expansion to the outside of the city to renewal within the city. Studies have shown that old neighbourhoods in cities are inevitably transforming into aging neighbourhoods. On the one hand, a large number of old neighbourhoods need to be updated to improve the internal environmental conditions. On the other hand, with the development of an aging society, the health problems of the elderly have attracted more and more attention from the society. It should be noted that among the elderly population, the physical condition of the elderly live in skipped-generation household (sgh) is often more fragile and more susceptible to environmental influences. In the renewal plan of old neighbourhoods, how to use resources scientifically has always been a problem that has plagued decision makers and designers. Therefore, the objective of this study is to establish a set of evaluation models related to the health of sgh,